2015
DOI: 10.1016/j.gene.2015.06.018
|View full text |Cite
|
Sign up to set email alerts
|

Regulation and function of the human HSP90AA1 gene

Abstract: Heat shock protein 90α (Hsp90α), encoded by the HSP90AA1 gene, is the stress inducible isoform of the molecular chaperone Hsp90. Hsp90α is regulated differently and has different functions when compared to the constitutively expressed Hsp90β isoform, despite high amino acid sequence identity between the two proteins. These differences are likely due to variations in nucleotide sequence within non-coding regions, which allows for specific regulation through interaction with particular transcription factors, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
177
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 223 publications
(181 citation statements)
references
References 95 publications
4
177
0
Order By: Relevance
“…This property allows targeting Hsp90’s cancer‐cell–protective and antiapoptotic functions, while avoiding the unwanted feedback effect caused by the N‐domain inhibitors. ( ) Corroborating our findings with the amino coumarin, NB, silibinin, a structurally unrelated flavonolignan, which also binds to the C‐terminal region of Hsp90, shows pharmacological similarity to NB and also induced the degradation of Bclaf1 (Supporting Fig. E).…”
Section: Discussionsupporting
confidence: 82%
“…This property allows targeting Hsp90’s cancer‐cell–protective and antiapoptotic functions, while avoiding the unwanted feedback effect caused by the N‐domain inhibitors. ( ) Corroborating our findings with the amino coumarin, NB, silibinin, a structurally unrelated flavonolignan, which also binds to the C‐terminal region of Hsp90, shows pharmacological similarity to NB and also induced the degradation of Bclaf1 (Supporting Fig. E).…”
Section: Discussionsupporting
confidence: 82%
“…Hsp90 is an abundant cellular chaperone that interacts with many proteins, including transcription factors, kinases, E3-ligases, structural proteins, ribosomal components and metabolic enzymes [34]. We have shown that there, VP1 massively binds fiber structures that were identified as microtubules.…”
Section: Discussionmentioning
confidence: 99%
“…For example, based on the data in HSP90Int.db, Zuehlke et al [21] compiled a comparison of the HSP90α versus HSP90β interactomes. Other extensive reviews on HSP90 including interactors are those of Refs.…”
Section: Hsp90 Interactomicsmentioning
confidence: 99%
“…Extensive data on HSP90 are compiled on public databases such as phosphosite.org which listed, as of 4th of May 2017 no less than 168 PTMs sites for HSP90β and 179 for HSP90α. The main PTMs known on HSP90 have been reviewed in detail before, together with their functional significance, when known [6,21,44,7782]. Rather, here, we will cover the few studies assessing the impact of HSP90 inhibition on the global proteome PTMs (Figure 2).…”
Section: Global Impact Of Hsp90 Inhibition On the Proteomementioning
confidence: 99%